Graphic Communications in the Context of Nepal - Rajbhandari, Jitendra Man (SIRJANĀ – A Journal Of Arts and Art Education, 2018)
Graphic communication, a powerful tool for conveying information through visual aids has undergone a radical change since its early application by cave artists of Paleolithic age. With the development of print technology, both the scope and significance of graphic technology have been expanding. In the context of Nepal, graphic communication has received an attention since the advent of printing press. Several artists, illustrators and graphic designers have made great contributions on the development of this form of Applied Arts. Since the last few years the Fine Arts institutions in Nepal have been introducing Graphic Communications into their curriculum which is sure to uplift the quality of graphic design in promotion of the products and services in the Nepali market.